Development of a COVID-19 University-Based Clinic in Indonesia: A Pilot Project of The Gadjah Mada Electronic Nose Center - Wicaksana, Anggi Lukman; Kusumawati, Nurul Dyah; Wibowo, Ella Permatasari; Nirwati, Hera (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The clinic development of COVID-19 screening is essential during the pandemic. AIM: This study aimed to explore and elaborate the development process of the Gadjah Mada Electronic Nose (GeNose) Center as a pilot project for a COVID-19 university-based clinic in Indonesia. METHODS: A narrative and explorative study was conducted. Under the university platform, we initiated the GeNose center through training, simulation, and debriefing. Identification of team member recruitment, location, and apparatus development were described using the retrospective approach. RESULTS: Fifty-one team members were recruited, including person in charge, verifiers, administrative staffs, hotline team, security staffs, and janitors. Standard operating procedures, service system, and safety measures were developed to maintain the quality. Services include the application of COVID-19 protocols, registration and confirmation, education for using the air bag, collecting the air sample, and analysis of samples using the GeNose machine. CONCLUSION: The GeNose center, a model for screening test, provides services for the screening of COVID-19.